Enhanced magnetoelectric response in 2-2 bilayer 0.50Pb(Ni1/3Nb2/3)O3–0.35PbTiO3–0.15PbZrO3/NiFe2O4 thin films. (22nd February 2018) - Ade, Ramesh; Sambasiva, V; Kolte, Jayant; Karthik, T; Kulkarni, Ajit R; Venkataramani, N
Abstract: In this work, room temperature magnetoelectric (ME) properties of 0.50Pb(Ni1/3 Nb2/3 )O3 –0.35PbTiO3 –0.15PbZrO3 (PNNZT)/NiFe2 O4 (NFO) 2-2 bilayer thin films grown on Pt/Ti/SiO2 /Si substrate, using pulsed laser deposition technique, are reported. Structural studies confirm single phase PNNZT/NFO 2-2 bilayer structure formation. PNNZT/NFO 2-2 bilayer thin film shows a maximum ME voltage coefficient ( α E ) of ~0.70 V cm −1 . Oe –1 at a frequency of 1 kHz. The present study reveals that PNNZT/NFO bilayer thin film can be a potential candidate for technological applications.